PROFESSIONAL PEDAGOGICAL ERUDITION AS AN INTEGRATIVE-PEDAGOGICAL FACTOR IN DEVELOPING STUDENTS' PREPARATION. (Universal International Scientific Journal, 2026)
This article analyzes the theoretical essence of the concept of professional pedagogical erudition, its structural components, and its integrative and pedagogical significance in the development of students' professional training. It also substantiates the effective conditions for the formation of pedagogical erudition.
Keywords: professional pedagogical erudition, professional training, integrative approach, pedagogical competence, reflection, innovative activity.